(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To apply the broth microdilution method to determine the antibiotic resistance rates of Helicobacter pylori at the University Medical Center Ho Chi Minh City - Campus 2. Subject and methods: A cross-sectional descriptive study was conducted on 31 H.pylori strains stored at the University Medical Center Ho Chi Minh City - Campus 2. The strains were reactivated, identified, and their minimum inhibitory concentrations (MICs) were determined for five antibiotics, Amoxicillin, Clarithromycin, Levofloxacin, Metronidazole, and Tetracycline, using the broth microdilution method on laboratory-prepared microplates. MIC results were interpreted as susceptible or resistant according to the EUCAST v15.0 breakpoint criteria. Results: All 31 isolated strains grew in the broth microdilution medium, and bacterial growth could be visually assessed with a light box. The resistance rates of H.pylori to Clarithromycin, Metronidazole, Amoxicillin, Levofloxacin, and Tetracycline were 71%, 54.8%, 51.6%, 51.6%, and 0%, respectively. The proportion of strains susceptible to all tested antibiotics was 12.9%, while 22.6% were resistant to all antibiotics except Tetracycline. When classified by first-line treatment regimen, the resistance rate for the PALB regimen (Amoxicillin and Levofloxacin) was 35.5%, whereas no resistance was observed for the PTMB regimen (Metronidazole and Tetracycline) (0%). Conclusion: This study initially demonstrated the feasibility of the broth microdilution method for determining the MICs of antibiotics against H.pylori. The resistance rate to Metronidazole differed from that reported in recent Vietnamese studies, which may be attributed to differences in incubation conditions. Further studies are needed to determine which method better reflects clinical resistance. The PTMB regimen showed a favorable susceptibility profile and remains a reliable first-line treatment option for H.pylori infection in Vietnam.